Diversity of sacrifice : form and function of sacrificial practices in the ancient world and beyond - Murray, Carrie Ann, 1976-; University of Buffalo. Institute for European and Mediterranean Archaeology (Albany : State University of New York Press, 2016)
"Explores sacrificial practices across a range of contexts from prehistory to the present. The term 'sacrifice' belies what is a complex and varied transhistorical and transcultural phenomenon. Bringing together scholars from such diverse fields as anthropology, archaeology, epigraphy, literature, and theology, Diversity of Sacrifice explores sacrificial practices across a range of contexts from prehistory to the present. Incorporating theory, material culture, and textual evidence, the volume seeks to consider new and divergent data related to contexts of sacrifice that can help broaden our field of vision while raising new questions. The essays contributed here move beyond reductive and simple explanations to explore complex areas of social interaction. Sacrifice plays a key role in the overlapping sacred and secular spheres for a number of societies in the past and present. How religious beliefs and practices can be integral parts of life on individual and community levels is of fundamental importance to understanding the past and present. In addition to aiding scholarly research, Diversity of Sacrifice enables students to explore this rich theme across Europe and the Mediterranean with clear discussions of theory and data"--Publisher's website
The Value and Power of Sacrifice / Carrie Ann Murray -- Part I. Defining and Redefining the Boundaries of Sacrifice -- Anthropology and Sacrifice / Phillips Stevens, Jr. -- A View from a Fen : On the Concept of Sacrifice and the Possibility of Understanding Neolithic Wetland Depositions / Åsa Berggren -- Gifts from the Gods : A New Look at Some Weapons and Vessels from the Metal Ages / Christoph Huth -- Post-Domestic Sacrifice : Exploring the Present and Future of Gifts for the Gods / Samantha Hurn -- Part II. Sacrifice Across the Mediterranean World -- Every Good and Pure Thing : Sacrifice in the Ancient Egyptian Context / Mary-Ann Pouls Wegner -- The Mythology of Carthaginian Child Sacrifice : A Physical Anthropological Perspective / Jeffrey H. Schwartz -- The Art of Ancient Greek Sacrifice : Spectacle, Gaze, Performance / Tyler Jo Smith -- Etruscan Human Sacrifice : The Case of Tarquinia / Nancy de Grummond -- Part III. Exploring Exceptional Cases of Sacrifice -- Human Sacrifice as "Crisis Management"? : The Case of the Early Neolithic Site of Herxheim, Palatinate, Germany / Andrea Zeeb-Lanz, Rose-Marie Arbogast, Silja Bauer, Bruno Boulestin, Anne-Sophie Coupey, Anthony Denaire, Fabian Haack, Christian Jeunesse, Dirk Schimmelpfennig, Rouven Turck -- Dog Sacrifice at the Protohistoric Site of Mas Castellar (Pontós, Spain) / Enriqueta Pons, Lídia Colominas, Maria Saña -- Understanding the Death and Burial of Northern European Bog Bodies / Guinevere Granite -- Part IV. Formularizing and Regularizing Sacrifice -- Sacrificing the Sign : The Alphabet as an Offering in Ancient Israel or A Classicist's Read on the Ritual Law of the Sotah / Roger Woodard -- Ancient Greek Laws on Sacrifice / Michael Gagarin -- In What Way Is Christ's Death a Sacrifice? : Theories of Sacrifice and Theologies of the Cross / S. Mark Heim.
Papers from a conference held as the annual symposium for the Institute for European and Mediterranean Archaeology (IEMA) at the University at Buffalo, SUNY, in 2011.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 12, 2016).
JSTOR
Keywords: Sacrifice -- Europe -- History -- To 1500 -- Congresses; Sacrifice -- Mediterranean Region -- History -- To 1500 -- Congresses; Social archaeology -- Europe -- Congresses; Social archaeology -- Mediterranean Region -- Congresses; Archaeology and religion -- Europe -- Congresses; Archaeology and religion -- Mediterranean Region -- Congresses; Material culture -- Europe -- History -- To 1500 -- Congresses; Material culture -- Mediterranean Region -- History -- To 1500 -- Congresses; Social interaction -- Europe -- History -- To 1500 -- Congresses; Social interaction -- Mediterranean Region -- History -- To 1500 -- Congresses; Electronic books; Archéologie sociale -- Europe -- Congrès.; Archéologie et religion -- Europe -- Congrès.; Livres numériques.; e-books.; RELIGION -- Reference; Archaeology and religion; Material culture; Sacrifice; Social archaeology; Social interaction; Europe; Mediterranean Region; To 1500; Conference papers and proceedings; History